Novel Electrothermodynamic Power Generation. Issue 13 (4th May 2015) - Kim, Yoonho; Kim, Juyoung; Yamanaka, Satoru; Nakajima, Akira; Ogawa, Takashi; Serizawa, Takeshi; Tanaka, Hirohisa; Baba, Masaaki; Fukuda, Tatsuo; Yoshii, Kenji; Takeda, Masatoshi; Yamada, Noboru; et al.
<x xml:space="preserve">Abstract</x> To investigate how exhaust heat from automobiles can be converted to renewable energy, an innovative electrothermodynamic cycle is presented, which is based on temporal temperature variations, the pyroelectric effect, instead of spatial temperature gradient, and the Seebeck effect. A generating mechanism is investigated using operando time‐resolved synchrotron X‐ray diffraction. Practical energy and true energy breakeven are achieved via real engine dynamometer experiments.